Esterification of fatty acids with glycerol over Fe-Zn double-metal cyanide catalyst - Kotwal, Mehejabeen; Deshpande, Suvarna S.; Srinivas, D. (Catalysis Communications, 2011)
Solid Fe-Zn double-metal cyanide (DMC) complex exhibits high catalytic activity for esterification of fatty acids (FA) with glycerol. DMC catalysts with varying acidities were prepared by synthesizing the material at four different temperatures (10, 25, 50 and 80 degrees C). The catalyst prepared at 50 degrees C exhibited highest catalytic activity. Catalytic activity of DMC was influenced by both acidity and surface area. Complete conversion of FA was achieved at 140-200 degrees C under atmospheric pressure. Chain length of FA was found to influence the rate of reaction and product selectivity. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Acid-catalyzed reaction; Double-metal cyanide (DMC); Esterification of fatty acid; Fatty acid glycerides; solid acid catalyst